SYNTHESIS AND CHARACTERIZATION OF 4-ARYL TRIAZOLE RING SYSTEM AND ITS ANTIMICROBIAL ACTIVITY - SARJU N. PRAJAPATI; KALPESHGIRI V. GOSWAMI; ANUP N. PATEL (International Journal of Pharma and Bio Sciences, 2013)
Synthesis of some new 4-Aryl triazoles and its derivatives were synthesized. 4-aryl triazoles were obtained by cyclization reaction of the potassium salt of substituted dithiocarbazinic acids with aromatic amines. These compounds have been characterized on the basis of elemental analyses, IR, 1H NMR and MASS Spectrometry. Compounds have been screened for their antibacterial activity.